Voltaire and English literature - Gunny, A (Voltaire Foundation, 2017)
Preface Introduction 1. English tragedy and Voltaire i. Voltaire's conception of tragedy ii. Voltaire's reactions to Shakespeare iii. Dryden, Otway and Voltaire iv. Addison, Fenton and Voltaire 2. English comedy and Voltaire i. Voltaire on comedy ii. English comic dramatists and Voltaire 3. Voltaire and the English epic i. Voltaire and the epic ii. Milton's impact on Voltaire 4. English Augustan satirists and Voltaire i. Voltaire's attitude to satire ii. Butler, Rochester and Voltaire iii. Dryden's satirical influence on Voltaire iv. 'Minor' English satirical poets and Voltaire v. Pope's satirical impact on Voltaire 5. Voltaire's use of English prose i. Voltaire's thought on prose fiction ii. The influence of Swift and Sterne on Voltaire iii. Voltaire, Richardson and Fielding Conclusion Appendix Bibliography Index